Best Rest Periods According to Pulse And Some Cardio Muscle Indicators After Aerobic and Anaerobic Effort In Basketball Players - Hassan, Flah (Journal of Physical Education, 2016)
The purpose of the research is to focus on an important question to answer about values of indicators of the heart muscle during rest periods supported on the basis of the return heart rate to certain rates between 100-150 P after anaerobic and aerobic physical effort. Therefore, the study aimed at identifying which of best periods of rest according to heart rate when training is anaerobic or aerobic for basketball players. The study sample were selected from basketball aged (22) years, weight (76kg), a length of (187 cm) and numbered 14 players were homogenized with variables of heart rate (69) , stroke volume (76 ml), the cardiac production (5.85 liter/m ) and maximum oxygen consumption (9.58 ml / kg / m )As for heart muscle indicators that have been studied are (HR, SV, CO, CI, CTI, VET, EF,, EDV) study included a test (Wingate)for the anaerobic ability on the stationary bike Monark for a period of 30 seconds maximum effort in the Physiological laboratory Variables were measured as the heart at rest using a device (Physioflow) which gives results through wireless technology on a computer screen via electrodes mounted on the player chest. As for the aerobic physical effort has been conducting ( Bruce test ) on a walk moving and included work for 21 minutes divided into seven stages each with 3 minutes with an increased angle of inclination device at every stage of 2%, as it begins work inclination angle of 10% as it is obtained variables study by a (Physioflow) via electrodes mounted on the player chest. The values of heart variables were obtained through the effort on the bike and the period of rehabilitation. The results have been dealing statistically by using the law (F) and test (LSD).